POLICY ANALYSIS ON STUNTING REDUCTION AND ITS IMPACT ON ECONOMIC DEVELOPMENT IN SIKKA REGENCY - Syahbanda, Samsul Hidayat; Tameno , Nikson; Theresia, Novi (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
The objective of this study is to examine the stunting reduction policy and its challenges in relation to economic development in Sikka Regency. The research method used is descriptive qualitative. The findings show that the implementation of the stunting reduction policy includes programs such as the